Real-Time PCR-Based Mismatch Amplification Mutation Assay for Specific Detection of CS6-Expressing Allelic Variants of Enterotoxigenic Escherichia coli and Its Application in Assessing Diarrheal Cases and Asymptomatic Controls - Sabui, Subrata (American Society for Microbiology, 2012)
Enterotoxigenic Escherichia coli (ETEC) expressing the colonization factor CS6 is widespread in many developing countries, including India. The different allelic variants of CS6, caused by point mutations in its structural genes, cssA and cssB, are designated AIBI, AIIBII, AIIIBI, AIBII, and AIIIBII. A simple, reliable, and specific mismatch amplification mutation assay based on real-time quantitative PCR (MAMA-qPCR) was developed for the first time for the detection of CS6-expressing ETEC, along with the identification of allelic variations. The assay was based on mismatched nucleotide incorporation at the penultimate base at the 3′ ends of the reverse primers specific for cssA and cssB and was validated using 38 CS6-expressing ETEC isolates. This strategy was effective in detecting all the alleles containing single-nucleotide polymorphisms. Using MAMA-qPCR, we also tested CS6 allelic variants in 145 ETEC isolates from children with acute diarrhea and asymptomatic infections, with the latter serving as controls. We observed that the AIBI and AIIIBI allelic variants were mostly associated with cases rather than controls, whereas the AIIBII variants were detected mostly in controls. In addition, the AIBI and AIIIBI alleles were frequently associated with ETEC harboring the heat-stable toxin gene (est) alone or with the heat-labile toxin gene (elt), whereas the AIIBII allele was predominant in ETEC isolates harboring the elt gene. This study may help in understanding the association of allelic variants in CS6-expressing ETEC with the clinical features of diarrhea, as well as in ETEC vaccine studies.